Biomass production of fungus \(Termitomyces clypeatus\) in a stirred-tank bioreactor - Nhi, Nguyen Thi Ngoc; Dung, Tran Nhan (Academia Journal of Biology, 2021)
Termitomyces clypeatus is a fungus species, which has been used as food and medicinal mushroom. In the current study, submersed fermentation of the fungus in a stirred-tank bioreactor was determined for its culture biomass and nutrient contents. T. clypeatus obtained its highest biomass after from 13 to 15 days of cultivation, when the dry biomass of its mycelium system was more than 6%. Agitation speeds of 150 or 180 rpm were the most suitable for the fungus. The determination of chemical compositions showed that the dry biomass of its mycelium system had high protein content, with 57.8% on its dry-weight basis. Besides, 11 types of amino acids higher than 0.1% of wet weight culture were found in fermentation products. Moreover, dried mycelia of the fungus contained 27.4% carbohydrates. The protein and carbohydrate containing in the mycelium and fruit body of T. clypeatus were not statistically different. These results showed that a stirred-tank bioreactor could be applied to culture the fungus.